Literature Review : Relationship Between Mental Toughness And Athlete Performance In Basketball Matches - Muhamad Sahrul Gunawan; Siti Nuraysah; Ade Tuti Lestari (UNIB Press, 2025)
The purpose of this study is to examine the relationship between mental toughness and basketball athlete performance by analyzing scientific journals published between 2020 and 2025. Athlete performance is determined not only by physical and technical abilities, but also by psychological factors, where mental toughness plays a crucial role in dealing with competitive pressure. Therefore, this study is highly relevant to understanding more deeply how these psychological attributes influence athlete performance on the court. The method used in this study was a systematic literature review of various relevant scientific journals from 2020-2025. The results of the analysis of various studies indicate that mental toughness has a significant positive relationship with improved athlete performance in basketball matches. This relationship has been shown to influence various aspects of performance, including technical abilities such as shooting accuracy and decision-making under pressure, mental aspects such as focus and stress resilience, and social aspects such as leadership and teamwork. This research provides important practical implications for coaches and athletes to develop effective psychological training programs and solid social support, to optimize athlete potential holistically.